2017
DOI: 10.1007/s13760-017-0827-2
|View full text |Cite
|
Sign up to set email alerts
|

Progressive deficit in isolated pontine infarction: the association with etiological subtype, lesion topography and outcome

Abstract: It is important to predict progressive deficit (PD) in isolated pontine infarction, a relatively common problem of clinical stroke practice. Traditionally, lacunar infarctions are known with their progressive course. However, few studies have analyzed the branch atheromatous disease subtype as a subtype of lacunar infarction, separately. There are also conflicting results regarding the relationship with the topography of lesion and PD. In this study, we classified etiological subtypes and lesion topography in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…3,4 In addition to this mechanistic diversity, one additional challenge in the care of patients with acute pontine infarcts is the tendency of clinical deficits to fluctuate or progress in the first few days after symptom onset, with reports highlighting early motor deterioration ranging from 19% to 32% of cases. [5][6][7][8][9][10][11] The determination of high-risk patients for progression is important as these patients are well-known to have worse neurological outcomes in the long term. 8,12 Female sex, history of hypertension and diabetes mellitus, and higher admission National Institutes of Health Stroke Scale (NIHSS) scores have been highlighted as clinical factors that might be predictive of neurological worsening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In addition to this mechanistic diversity, one additional challenge in the care of patients with acute pontine infarcts is the tendency of clinical deficits to fluctuate or progress in the first few days after symptom onset, with reports highlighting early motor deterioration ranging from 19% to 32% of cases. [5][6][7][8][9][10][11] The determination of high-risk patients for progression is important as these patients are well-known to have worse neurological outcomes in the long term. 8,12 Female sex, history of hypertension and diabetes mellitus, and higher admission National Institutes of Health Stroke Scale (NIHSS) scores have been highlighted as clinical factors that might be predictive of neurological worsening.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,10,11,13 Several other studies underlined the importance of radiological features in predicting progression and suggested caudal location, longer vertical extent, and a pattern suggestive of branch artery occlusion as lesion characteristics associated with a higher rate of early motor deterioration. 6,8,10,13 The magnitude of the decrease in apparent diffusion coefficient (ADC) is closely related to fate of clinical and tissue outcome in territorial strokes. [14][15][16] In this study, our aim was to assess whether a similar ADC based approach could be used as an additional radiomic feature to forecast clinical deterioration in acute pontine infarctions.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, early neurological deterioration is one of the most concerning clinical problems in patients with branch atherosclerotic diseases. Progressive deficit has been associated with basilar artery branch disease and poor functional outcomes ( 41 ). Therefore, the progression of vascular stenosis or thrombosis caused by intracranial atherosclerosis is related to END.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have identified the presence of comorbidities (such as diabetes and hypertension), female sex, infarct size, and neurological severity at onset to be associated with progressive deficit in patients with isolated pontine infarctions. However, some studies have reported inconsistent findings ( 41 ). In addition, the infarct area extending to the basal surface was 2.5 times greater than deep infarctions without extension to the basal surface ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation